Oral hygiene instructions and dietary sugar advice received by adolescents in 1989 and 1997 - Honkala S, Honkala E, Rimpelä A, Vikat A. (Blackwell Synergy, 2002)
The aim of this study was to find out how commonly adolescents receive oral hygiene instructions and dietary sugar advice in the Finnish public oral health care system and whether there have been any changes between 1989 and 1997.